PENGARUH FILLER ORAGANO-CLAY TERHADAP SIFAT MEKANIK MATERIAL NANOCOMPOSIT BERMATRIX EPOXY - Salam, Haipan (JURNAL PENELITIAN SAINTIKA, 2011)
The aim of this research was to study the influence of the organoclay contents to the mechanicalproperties of nanocomposites materials. In situ polymerization used to synthesize nanocompositesepoxy-organo clay materials. Tensile test and compressive test were conducted based on ASTMstandards. The nanocomposite properties were compared to epoxy matrix polymer. The amount oforganoclay contained influence to mechanical properties of nanocomposite materials. The addition of10.5 wt.% organoclay improved the tensile modulus about 185%. These decreases in the strength maybe attributed to the fact that agglomerates and voids were formed. The compression test result showedthat the addition of 3 .1 wt.% organoclay demonstrated a I 02% increase in compression strength and a93% increase in load maximum compare to epoxy resin. An addition of 7.3 wt. % organoclaydemonstrated an increase of modulus of the epoxy resin by 93%. Meanwhile, the addition of 10.5 wt.% organoclay caused the decreasing in yield compression up to 31 %.